Evaluation feasibility and ecological gap in marine conservation area of Southeast Sulawesi Province - Zulhamsyah Imran; Cahyo Wijayanto; Fredinan Yulianda (Depik, 2023)
Aquatic Tourism Park (ATP) of the Southeast Sulawesi Province has significant contribution to achieve the total targeted of 30 million of Marine Protected Areas (MPA) in Indonesia. The conservation area is located in 3 coastal districts of Konawe, South Konawe, and Kendari City Districts. The time-consuming process of legalizing the conservation area has driven the need to re-evaluate the ecological conditions from 2012 to 2020. The objective of this study is to this aims to determine the status, gaps and ecological feasibility of conservation areas in the Southeast Sulawesi region. One of the noticeable gaps is the change of ecological conditions in the reservation area.  The gap could be identified by comparing ecological conditions before and after the area was reserved for a conservation area. Ecosystem suitability was measured by using ecological criteria, such as number of protected fish species, mangrove density, seagrass coverage, coral coverage, and naturalness. The score of suitability assessment was 31, which showed that the reserved location was suitable for a Marine Conservation Area.  However, gap analysis results showed 10% decline in coral coverage and 17% decrease in seagrass coverage, while mangrove density decreased as much as 102 trees/ha during that period. Evaluation on the ecosystem condition was conducted by applying suitability analysis of the modified E-KKP3K dan Sambah et al. (2020) methods, resulting a status of suitable or conservation area allocation (score 31). Criteria used were chosen based on its contribution in facilitating important ecological processes and as ecosystem buffer system in the area. This study will give the implementation on MPA management optimalisation and it can be contributed on fisheries management.Keywords:Conservation areaFeasibility areaGapSoutheast Sulawesi